Bacillus coagulans alleviates hepatic injury caused by Klebsiella pneumoniae in rabbits - Xiaoguang Chen; Wenjuan Wei; Fan Yang; Jianing Wang; Qiongxia Lv; Yumei Liu; Ziqiang Zhang (PLoS ONE, 2025)
Background As an opportunistic bacterial pathogen, Klebsiella pneumoniae (KP) is prone to causing a spectrum of diseases in rabbits when their immune system is compromised, which poses a threat to rabbit breeding industry. Bacillus coagulans (BC), recognized as an effective probiotic, confers a variety of benefits including anti-inflammatory and antioxidant properties. Aim The purpose of this study was to investigate whether dietary BC can effectively alleviate hepatic injury caused by KP. Methods In this study, the rabbits were initially pretreated with varying doses of BC (1×106, 5×106, and 1×107 CFU/g), followed by a challenge with KP at a concentration of 1011 CFU/mL. Liver tissues were harvested and processed for histological assessment using H&E and VG stains to assess structural alterations. Biochemical assays were employed to quantify the enzymatic activities of T-SOD and GSH-Px, as well as the MDA content. Furthermore, ELISA was utilized to detect the levels of inflammatory cytokine (IL-10, IL-6, IL-1β and TNF-α) and apoptotic-related gene (Bcl-2, Bax). Results Morphological observation indicated that BC can effectively mitigate KP-induced hepatic sinusoidal dilatation and congestion, as well as ameliorate the degree of hepatic fibrosis. Further analysis showed that BC significantly lowered MDA level in KP-treated rabbits, while enhanced the activities of T-SOD and GSH-Px. Additionally, ELISA result showed that BC pretreatment significantly reduced the levels of pro-inflammatory cytokines TNF-a, IL-6, IL-1β and pro-apoptotic gene Bax, while increasing the levels of anti-inflammatory cytokine IL-10 and anti-apoptotic gene Bcl-2 in KP-treated rabbits. Conclusion Above data indicate that BC supplementation effectively attenuated oxidative stress and inflammatory response induced by KP through augmenting the activities of antioxidant enzymes and diminishing the levels of pro-inflammatory factors. Furthermore, it reduced the Bax/Bcl-2 ratio in the liver, thereby inhibiting KP-induced apoptosis. The treatment group receiving 5x106 CFU/g BC benefitted most from the protective effect.